Measurement and Analysis of Hydrogen Distribution in Stress Environment Using Vickers Microhardness Technique. (27th September 2018) - Gu, Lei; Wang, Jing; Li, Xiaoyang; Zeng, Yanjun
Abstract : In this paper, the stress distribution field in front of the crack tip was obtained by loading a modified WOL specimen using a bolt. Considering the relationship between microhardness and hydrogen content or internal stress in the metal, a model based on the change of microhardness increment is proposed to describe the trend of hydrogen concentration distribution in the stress environment. The agreement between theoretical model and experimental results is verified by the Vickers microhardness tester. Based on the model, there is a simple additive relationship between the hydrogen-induced microhardness increment and the stress-induced microhardness increment. Therefore, the microhardness tester can be employed to evaluate the hydrogen distribution in metals quantitatively. The experimental results demonstrated that the Vickers microhardness method has accurately revealed the hydrogen concentration behavior accurately in a known equibiaxial stress environment. The hydrogen distribution of specimens in the stress environment was analyzed by taking the change of the microhardness increment along the crack propagation direction of specimens as the indicator.